Assessment of water mass distribution and intrusions of circumpolar deep water in the Amundsen Sea based on the ocean reanalysis product FOAM-GLOSEA5v13 - Li, Ziang; Wang, Chuning; Zhou, Meng (Frontiers in Marine Science, 2024)
The Amundsen Sea of West Antarctica is one of the regions of particularly interest to the oceanography community due to accelerated basal melting of its ice shelves. Quantitative estimates of the composition of water masses and their sources are essential for understanding the heat and salt budgets and the stability of ice shelves in this region. In this study, the water mass distributions on the Amundsen Sea continental shelf are estimated based on FOAM-GLOSEA5v13, a global oceanographic reanalysis product, using a modified statistical based optimal water mass analysis method. The reanalysis product effectively captures the signal of primary water masses, including the Winter Water (WW) and the Circumpolar Deep Water (CDW) below the Antarctic Summer Surface Water (SSW). The horizontal and vertical distributions and temporal evolution of three water mass endmembers (WW, CDW and DSW) and their mixing ratios are calculated, based on which an intrusion location detection method was established. Using the reanalysis product and intrusion detection method, all potential CDW intrusion sites along the shelf break are identified. Based on the reanalysis product, an intrusion site over the shelf break, away from major deep troughs was captured and confirmed by numerical particle tracking experiments.